Reinterpreting the Sacred: The Kaaba as a Symbolic and Architectural Motif in Contemporary Mosque Design - The Case of Kazan Mosque - Kumar, Chetan (Journal of Progress in Civil Engineering, 2025)
At the "ArchMoscow 2023" architectural exhibition, a new design proposal for the Grand Mosque in Kazan was introduced. The proposed structure features a large cube, reminiscent of the Kaaba, with a domed prayer hall inside. While the project received approval from Tatarstan authorities, it has sparked debate among architects and scholars. The controversy centers around the theological implications of replicating the Kaaba’s form in mosque architecture. This study critically examines the uniqueness of the design, its alignment with competition objectives, and the broader discourse on Kaaba-inspired mosques.